2015
DOI: 10.1111/jocn.12927
|View full text |Cite
|
Sign up to set email alerts
|

Pressure ulcer risk assessment: retrospective analysis of Braden Scale scores in Portuguese hospitalised adult patients

Abstract: Nurses should use Braden Scale assessment and consider patients' characteristics and diagnoses to plan more focused preventive interventions and improve nursing care. This study could be the first step to create a preventive protocol based on institutional reality, patients' characteristics, level of risk and affected sub-scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 30 publications
3
22
0
4
Order By: Relevance
“…In the current study, the majority of the participants failed to use a risk assessment scale. Sardo et al, (2015) reported similar results to the ones obtained in this current study. This finding can be explained by some nurses' thinking that their clinical evaluation is preferable to the use of a risk assessment scale and that the use of the risk assessment scale is time-consuming.…”
Section: Perceived Barrierssupporting
confidence: 92%
“…In the current study, the majority of the participants failed to use a risk assessment scale. Sardo et al, (2015) reported similar results to the ones obtained in this current study. This finding can be explained by some nurses' thinking that their clinical evaluation is preferable to the use of a risk assessment scale and that the use of the risk assessment scale is time-consuming.…”
Section: Perceived Barrierssupporting
confidence: 92%
“…In particular, the BAS measures the mobility (walking and transferring) level of the hospitalized patient with a score of 1 (“patient is confined to bed”), 2 (“severely limited or nonexistent ability to walk; patient cannot bear his own weight and/or must be assisted into chair or wheelchair”), 3 (“patient walks occasionally during the day, but for very short distances, with or without assistance; he spends majority of each shift in bed or chair”), or 4 (“patient walks outside the room at least twice a day and inside the room at least once every 2 hours during waking hours”). The BAS is correlated with the total Braden scale 10 and has shown excellent interrater reliability (interclass correlation coefficient, 0.96) among hospital staff. 13 Analysis of the current dataset revealed excellent rater agreement across 3 working shifts (κ = 0.76 for first day of hospitalization in those hospitalized <3 days; κ = 0.70 for first day in those hospitalized ≥3 days).…”
Section: Methodsmentioning
confidence: 98%
“…While we had a large number of patient observations during the hospital stay, our measure of mobility impairment is not objectively ascertained as compared to others who have used activity monitors 23 . With that said, the Braden activity sub score has demonstrated good validity and reliability for mobility changes 14 and a strong correlation with the Braden scale which is a validated indirect measure of the mobility status of the patient 13 . Moreover, the mobility status of the patient prior to admission was unknown.…”
Section: Discussionmentioning
confidence: 94%
“…This is why the Braden activity subscale can be used also to assess the mobility level of the patient in a clinical setting. In particular, the Braden activity subscale has demonstrated a strong correlation with the Braden scale at admission and at discharge in assessing pressure ulcer risk and consequently the mobility status of the patient 13 and has excellent inter-reliability among hospital staff with an inter-class correlation coefficient of 0.96 14 . The Braden activity subscale measures the mobility (walking and transferring) level of the hospitalized patient with a score between 1 and 4 where: 1 = “the patient is confined to bed”; 2 = “ability to walk severely limited or non-existent; the patient cannot bear his own weight and or must be assisted into chair or wheelchair”; 3 = “the patient walks occasionally during the day, but for very short distances, with or without assistance; he spends majority of each shift in bed or chair”; 4 = “the patient walks outside the room at least twice a day and inside the room at least once every 2 hours during waking hours”.…”
Section: Methodsmentioning
confidence: 99%